Layered high-entropy oxide positive electrode material of sodium ion battery, preparation method of layered high-entropy oxide positive electrode material, positive electrode plate and sodium ion battery
By using a layered high-entropy oxide positive electrode material with the chemical formula of NaxNiaMnbMcO2 in sodium ion batteries, and preparing it by sol-gel method, the problem of poor structural stability of the positive electrode material of sodium ion batteries is solved, and high discharge capacity and electrochemistry are achieved Reversibility, suitable for sodium ion battery applications in the voltage range of 1.5 to 4.5V.
Patent Information
- Application Number
- CN202311509234.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2024-12-20
AI Technical Summary
The existing layered transition metal oxide sodium ion battery cathode materials have poor structural stability under high voltage conditions, severe capacity loss, and few high entropy oxide cathode materials with excellent electrochemical performance, making it difficult to meet the needs of sodium ion batteries. .
The layered high-entropy oxide positive electrode material with the chemical formula NaxNiaMnbMcO2 was prepared by sol-gel method to control the ratio of multiple metal elements to form a stable single-phase structure, inhibit phase change, improve cycle stability and electrochemical performance.
It achieves high discharge specific capacity and excellent electrochemical reversibility in the voltage range of 1.5 to 4.5V, significantly improves the structural stability and electrochemical performance of sodium ion batteries, and is simple and easy to produce on a large scale.
Smart Images

Figure CN119170795A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a sodium ion battery layered high entropy oxide positive electrode material and a preparation method thereof, as well as a positive electrode sheet and a sodium ion battery. Background Art
[0002] Sodium-ion batteries have attracted extensive attention from academia and industry due to their low cost, abundant sources, and ability to meet the growing demand for grid-scale energy storage systems. Layered transition metal oxides are one of the most attractive cathode materials for sodium-ion batteries due to their overall advantages in energy density and cost. However, the structural stability of layered transition metal oxides is easily affected by complex phase transitions and redox reactions, especially when working under high voltage conditions, resulting in poor structural stability and severe capacity loss.
[0003] High entropy oxides are single-structure oxides obtained by solid solution of five or more metal or non-metal oxides in equal or near molar ratios, in which each element shares equal atomic positions. High entropy oxides have a unique structure and often exhibit excellent properties, such as high fracture toughness, excellent high and low temperature properties, and good energy storage properties.
[0004] In recent years, the concept of high entropy oxides has begun to be applied to positive electrode materials for sodium ion batteries. However, there are many types of metal elements in high entropy oxides, and it is not possible to form a stable single-phase high entropy oxide by randomly combining multiple metal elements. At present, there are still few high entropy oxides with excellent electrochemical properties that can be used as positive electrodes for sodium ion batteries. There is an urgent need to provide layered high entropy oxide positive electrode materials for sodium ion batteries with high capacity and good electrochemical reversibility. Summary of the invention
[0005] In view of this, the present invention provides a sodium ion battery layered high entropy oxide positive electrode material and a preparation method thereof, a positive electrode sheet, and a sodium ion battery. The sodium ion battery layered high entropy oxide positive electrode material provided by the present invention has excellent electrochemical properties, high discharge specific capacity, and good electrochemical reversibility.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A layered high entropy oxide positive electrode material for a sodium ion battery, the general chemical formula of which is shown in Formula I:
[0008] Na x Ni a Mn b M c O2 Formula I;
[0009] In formula I: 0.6≤x≤0.7, 0.15≤a<0.33, 0.5≤b<0.67, 0<c≤0.35, a+b+c=1, M is at least four of Li, Zn, Cu, Mg, Ca, Fe, Al, Co, Y, Ru, Ti, Ir, Sb, Te, Sn, and Nb;
[0010] The layered high entropy oxide positive electrode material is a P2 phase.
[0011] Preferably, M is at least four of Zn, Cu, Mg, Al, Ti, Sn and Nb.
[0012] Preferably, the layered high entropy oxide positive electrode material of the sodium ion battery is Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Ti 0.1 O2 and Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Al 0.05 Nb 0.05 At least one of O2.
[0013] The present invention also provides a method for preparing the layered high entropy oxide positive electrode material for sodium ion batteries described in the above scheme, comprising the following steps:
[0014] Mixing a sodium source, a nickel source, a manganese source, a soluble compound corresponding to the M element and a citric acid solution, adjusting the pH value of the resulting mixed solution to 7 to 8, and then heating and stirring to obtain a gel precursor;
[0015] The gel precursor is pre-calcined and calcined in sequence to obtain the sodium ion battery layered high entropy oxide positive electrode material.
[0016] Preferably, the molar ratio of citric acid to metal ions in the mixed solution is (1.2-1.5):1, and the molar amount of the metal ions is calculated based on the total molar amount of sodium ions, nickel ions, manganese ions and M ions.
[0017] Preferably, the heating and stirring temperature is 60-80° C., the stirring speed is 400-800 rpm, and the time is 2-6 hours.
[0018] Preferably, the step of obtaining a wet gel after heating and stirring further comprises drying the wet gel and then grinding it to obtain a gel precursor.
[0019] Preferably, the pre-calcination temperature is 350-500°C and the time is 5-12h;
[0020] The calcination temperature is 800-900° C. and the calcination time is 10-16 hours.
[0021] The present invention also provides a positive electrode sheet, comprising the sodium ion battery layered high entropy oxide positive electrode material described in the above scheme or the sodium ion battery layered high entropy oxide positive electrode material prepared by the preparation method described in the above scheme.
[0022] The present invention also provides a sodium ion battery, comprising the positive electrode sheet described in the above scheme.
[0023] The present invention provides a layered high entropy oxide positive electrode material for a sodium ion battery, the general chemical formula of which is shown in Formula I: x Ni a Mn b M c O2 formula I; in formula I: 0.6≤x≤0.7, 0.15≤a<0.33, 0.5≤b<0.67, 0<c≤0.35, a+b+c=1, M is at least four of Li, Zn, Cu, Mg, Ca, Fe, Al, Co, Y, Ru, Ti, Ir, Sb, Te, Sn, Nb; the layered high entropy oxide positive electrode material is P2 phase. The present invention adopts at least 7 elements, and strictly controls the ratio of each element to obtain a layered high entropy oxide with a stable single-phase structure; the layered high entropy oxide positive electrode material for sodium ion batteries provided by the present invention has good structural stability, and the reaction process mainly undergoes solid solution phase reaction, which can effectively inhibit the occurrence of phase change, thereby improving cycle stability and enhancing sodium storage electrochemical performance. The results of the embodiments show that when the layered high entropy oxide positive electrode material of the present invention is applied to a sodium ion battery, the resulting sodium ion battery has a high discharge specific capacity in a wide voltage range of 1.5 to 4.5 V and also exhibits excellent electrochemical reversibility.
[0024] The present invention also provides a method for preparing the layered high entropy oxide positive electrode material for sodium ion batteries described in the above scheme. The present invention first adopts a sol-gel method to obtain a precursor, and then sinters it into a phase through a solid phase reaction method. The obtained positive electrode material particles are evenly distributed and also show good structural stability. In terms of reversible capacity and electrochemical reversibility, it is significantly superior to the material prepared by the ordinary high-temperature solid phase method. The preparation method provided by the present invention is simple to operate, and the target product can be obtained through simple mixing, calcination and other processes, and large-scale production can be easily realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD pattern of the positive electrode material prepared in Example 1;
[0026] Figure 2This is a SEM image of the positive electrode material prepared in Example 1;
[0027] Figure 3 The first five charge and discharge curves of a sodium ion battery assembled with the positive electrode material prepared in Example 1 at a current density of 0.1C;
[0028] Figure 4 The graph is a cycle performance diagram of the first 50 cycles of a sodium ion battery assembled with the positive electrode material prepared in Example 1 at a current density of 0.1C;
[0029] Figure 5 XRD pattern of the positive electrode material prepared in Example 2;
[0030] Figure 6 The first five charge and discharge curves of a sodium ion battery assembled with the positive electrode material prepared in Example 2 at a current density of 0.1C;
[0031] Figure 7 The figure is a cycle performance diagram of the first 50 cycles of a sodium ion battery assembled with the positive electrode material prepared in Example 2 at a current density of 0.1C;
[0032] Figure 8 XRD diagram of the positive electrode material prepared in Comparative Example 1;
[0033] Fig. 9 The first five charge and discharge curves of the sodium ion battery assembled with the positive electrode material prepared in Comparative Example 1 at a current density of 0.1C;
[0034] Fig.10 XRD diagram of the positive electrode material prepared in Comparative Example 2;
[0035] Fig.11 The first five charge and discharge curves of the sodium ion battery assembled with the positive electrode material prepared in Comparative Example 2 at a current density of 0.1C;
[0036] Fig.12 The figure is a cycle performance diagram of the first 50 cycles of a sodium ion battery assembled with the positive electrode material prepared in Comparative Example 2 at a current density of 0.1C;
[0037] Fig.13 XRD diagram of the positive electrode material provided for Comparative Example 3;
[0038] Fig.14 The first five charge and discharge curves of the sodium ion battery assembled with the positive electrode material prepared in Comparative Example 3 at a current density of 0.1C;
[0039] Fig.15 XRD pattern of the positive electrode material prepared in Comparative Example 4;
[0040] Fig.16This is a SEM image of the positive electrode material prepared in Comparative Example 4;
[0041] Fig.17 The first five charge and discharge curves of the sodium ion battery assembled with the positive electrode material prepared in Comparative Example 4 at a current density of 0.1C;
[0042] Fig.18 XRD diagram of the positive electrode material prepared in Comparative Example 5;
[0043] Fig.19 The first five charge and discharge curves of the sodium ion battery assembled with the positive electrode material prepared in Comparative Example 5 at a current density of 0.1C;
[0044] Fig. 20 XRD pattern of the positive electrode material prepared in Comparative Example 6;
[0045] Fig.21 The first five charge and discharge curves of the sodium ion battery assembled with the positive electrode material prepared in Comparative Example 6 at a current density of 0.1C;
[0046] Fig. 22 XRD pattern of the positive electrode material prepared in Comparative Example 7;
[0047] Fig.23 This is a SEM image of the positive electrode material prepared in Comparative Example 7;
[0048] Fig.24 The first five charge and discharge curves of the sodium ion battery assembled with the positive electrode material prepared in Comparative Example 7 at a current density of 0.1C;
[0049] Fig.25 XRD pattern of the positive electrode material prepared in Comparative Example 8;
[0050] Fig.26 This is a SEM image of the positive electrode material prepared in Comparative Example 8;
[0051] Fig. 27 This is a charge and discharge curve diagram of the first five cycles of a sodium ion battery assembled using the positive electrode material prepared in Comparative Example 8 at a current density of 0.1C. DETAILED DESCRIPTION
[0052] The present invention provides a layered high entropy oxide positive electrode material for a sodium ion battery, the general chemical formula of which is shown in Formula I:
[0053] Na x Ni a Mn b M c O2 Formula I;
[0054] In formula I: 0.6≤x≤0.7, 0.15≤a<0.33, 0.5≤b<0.67, 0<c≤0.35, a+b+c=1, M is at least four of Li, Zn, Cu, Mg, Ca, Fe, Al, Co, Y, Ru, Ti, Ir, Sb, Te, Sn, and Nb;
[0055] The layered high entropy oxide positive electrode material is preferably a P2 phase.
[0056] In the present invention, x is preferably 0.62-0.68, more preferably 0.66; a is preferably 0.16-0.3, more preferably 0.18; b is preferably 0.55-0.6, more preferably 0.57; c is preferably 0.5-0.35, more preferably 0.25. In the present invention, c represents the total stoichiometric ratio of all M elements.
[0057] In the present invention, the M is preferably at least four of Zn, Cu, Mg, Al, Ti, Sn and Nb; more preferably Zn, Cu, Mg and Ti, or preferably Zn, Cu, Mg, Al and Nb; the present invention has no requirements on the ratio of multiple M elements, and any ratio can be used.
[0058] In the present invention, the layered high entropy oxide positive electrode material of the sodium ion battery is preferably any one of the following materials: Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Ti 0.1 O2、Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Al 0.05 Nb 0.0 5O2.
[0059] The present invention also provides a method for preparing the layered high entropy oxide positive electrode material for sodium ion batteries described in the above scheme, comprising the following steps:
[0060] Mixing a sodium source, a nickel source, a manganese source, a soluble compound corresponding to the M element and a citric acid solution, adjusting the pH value of the resulting mixed solution to 7 to 8, and then heating and stirring to obtain a gel precursor;
[0061] The gel precursor is pre-calcined and calcined in sequence to obtain the sodium ion battery layered high entropy oxide positive electrode material.
[0062] The present invention mixes a sodium source, a nickel source, a manganese source, a soluble compound corresponding to the M element, and a citric acid solution, and adjusts the pH value of the obtained mixed solution to 7-8, and then heats and stirs to obtain a gel precursor. In the present invention, the sodium source, the nickel source, and the manganese source are independently preferably at least one of acetate, nitrate, oxalate, and an organic compound; specifically, the sodium source is preferably sodium acetate, the nickel source is preferably nickel acetate, and the manganese source is preferably manganese acetate; the soluble compound corresponding to the M element is preferably a salt or organic compound corresponding to the M element; the salt corresponding to the M element is preferably at least one of acetate, nitrate, and oxalate; when the M includes the Ti element, the compound used is preferably tetrabutyl titanate. In the present invention, the ratio of the sodium source, the nickel source, the manganese source, and the soluble compound corresponding to the M element is preferably prepared according to formula I, wherein the amount of the sodium source is preferably 5% excess on the basis of the theoretical molar amount.
[0063] In the present invention, the molar ratio of citric acid to metal ions in the mixed solution is preferably (1.2-1.5):1, more preferably (1.3-1.4):1; the molar amount of the metal ions is based on the total molar amount of sodium ions, nickel ions, manganese ions and M ions.
[0064] In the present invention, the reagent used to adjust the pH value of the mixed solution is preferably ammonia water, and the mass fraction of the ammonia water is preferably 25-28%; in a specific embodiment of the present invention, citric acid is preferably added to deionized water to obtain a citric acid solution, and then the sodium source, nickel source, manganese source, and soluble compounds corresponding to the M element are added to the citric acid solution, stirred at room temperature for 30 minutes, and then ammonia water is added dropwise to adjust the pH value of the mixed solution. The present invention has no special requirements for the concentration of the citric acid solution, as long as the citric acid can be dissolved.
[0065] In the present invention, the heating and stirring temperature is preferably 60-80°C, more preferably 70-80°C, the stirring speed is preferably 400-800 rpm, more preferably 500-700 rpm, and the time is preferably 2-6 h, more preferably 3-5 h.
[0066] In the present invention, a wet gel is obtained after the heating and stirring. The present invention preferably further comprises grinding the wet gel after drying to obtain a gel precursor; the drying temperature is preferably 120°C, and the time is preferably 10 hours; the drying is preferably carried out in a blast drying oven; the present invention has no special requirements for the grinding, as long as it can be ground evenly.
[0067] After obtaining the gel precursor, the present invention pre-calcines and calcines the gel precursor to obtain the sodium ion battery layered high entropy oxide positive electrode material. In the present invention, the pre-calcination temperature is preferably 350-500°C, more preferably 400-450°C, and the heating rate of heating to the pre-calcination temperature is preferably 5°C / min; the pre-calcination time is preferably 5-12h, more preferably 6-10h; the pre-calcination is preferably carried out in an oxygen atmosphere; the present invention preferably first presses the gel precursor into tablets and then pre-calcines; the present invention can remove organic components in the material by pre-calcining; after the pre-calcination is completed, the present invention preferably grinds the obtained material and presses it into tablets again, and then calcines; the calcination temperature is preferably 800-900°C, more preferably 830-850°C, the heating rate of heating to the calcination temperature is preferably 5°C / min, the calcination time is preferably 10-16h, more preferably 12-15h; the calcination is preferably carried out in air or oxygen atmosphere. After the calcination is completed, the present invention preferably cools the obtained material to room temperature and then grinds it to obtain the sodium ion battery layered high entropy oxide positive electrode material.
[0068] The present invention also provides a positive electrode sheet, comprising the sodium ion battery layered high entropy oxide positive electrode material described in the above scheme or the sodium ion battery layered high entropy oxide positive electrode material prepared by the preparation method described in the above scheme. In the present invention, the positive electrode sheet preferably includes a current collector and a positive electrode material layer coated on the surface of the current collector; the components in the positive electrode material layer preferably include a sodium ion battery layered high entropy oxide positive electrode material, a conductive additive and a binder; the mass ratio of the sodium ion battery layered high entropy oxide positive electrode material, the conductive additive and the binder is preferably 7:2:1; the conductive additive is preferably Super P, and the binder is preferably polyvinylidene fluoride; the present invention has no special requirements for the current collector, and it can be used as those well known to those skilled in the art, such as aluminum foil.
[0069] The present invention preferably adds a sodium ion battery layered high entropy oxide positive electrode material, a conductive additive and a binder into a solvent to obtain a positive electrode coating, and then applies the positive electrode coating on the surface of the current collector, and obtains the positive electrode sheet after drying; the solvent is preferably N-methylpyrrolidone.
[0070] The present invention also provides a sodium ion battery, comprising the positive electrode sheet described in the above scheme. In the present invention, the sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the negative electrode sheet is preferably metallic sodium; the separator is preferably glass fiber; and the electrolyte is preferably propylene carbonate containing 1M NaClO4.
[0071] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0072] Example 1
[0073] According to the element molar ratio of 0.66:0.18:0.57:0.05:0.05:0.05:0.1, sodium acetate, nickel acetate, manganese acetate, zinc acetate, copper acetate, magnesium acetate and tetrabutyl titanate are accurately weighed respectively (wherein, the amount of sodium acetate is 5% excess on the basis of the theoretical molar amount); citric acid is dissolved in 30 mL of deionized water, and the molar amount of citric acid is 1.5 times the molar amount of metal ions; the above raw materials are added to the citric acid solution and stirred at room temperature for 30 minutes; 25-28% mass fraction of ammonia water is added dropwise until the pH value of the mixed solution is adjusted to 7; the mixed solution is placed in a water bath at 80°C and heated and stirred to obtain a wet gel; the obtained wet gel is transferred to a 120°C blast oven and dried for 10 hours, and a gel precursor is obtained after uniform grinding. The gel precursor is pressed into a disc with a diameter of 14 mm at a pressure of 15 MPa. The obtained flake sample was placed in a tube furnace and heated to 450°C at a rate of 5°C / min for pre-calcination for 6 hours, cooled naturally to room temperature, ground and pressed into sheets, and then heated to 900°C at a rate of 5°C / min for calcination for 12 hours, cooled naturally to room temperature, and the cooled product was ground to obtain a layered high entropy oxide positive electrode material for sodium ion batteries, whose chemical formula is Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Ti 0.1 O2.
[0074] A series of characterization tests were performed on the cathode material obtained in this example: Figure 1 This is the XRD pattern of the obtained layered high entropy oxide positive electrode material for sodium ion batteries. The characteristic diffraction peaks are clearly visible, all of which are consistent with the space group P63 / mmc, and there are no extra diffraction peaks in the XRD spectrum, indicating that the positive electrode material is a P2 pure phase.
[0075] Figure 2 This is the SEM image of the obtained layered high entropy oxide positive electrode material for sodium ion batteries. Figure 2 The results in the table show that the cathode material powder obtained in this example is composed of small particles with a particle size of about 1 to 3 μm, each particle has a good single crystal morphology, and the material compaction density is excellent.
[0076] Preparation of button cells:
[0077] The prepared positive electrode material was mixed with a conductive additive (SuperP) and a binder (polyvinylidene fluoride) in a mass ratio of 7:2:1, and an appropriate amount of solvent N-methylpyrrolidone (NMP) was added. After stirring evenly, it was coated on an aluminum foil, placed in a vacuum oven at 70°C and dried for 12 hours, and then punched into a positive electrode sheet with a diameter of 12 mm. CR2032 button cells were assembled in an argon glove box, in which the electrolyte was a mixed solution of propylene carbonate (PC) containing 1M NaClO4 and 5% fluoroethylene carbonate (FEC), a metal sodium sheet was used as the negative electrode, and a glass fiber GF / F (Whatman) was used as a separator.
[0078] The above button batteries were tested for charge and discharge at room temperature on the Xinwei battery testing system. Figure 3 The first five cycles of charge and discharge curves of the obtained button battery at a current density of 0.1C; Figure 3 The results showed that Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Ti 0.1 The first charge and discharge capacities of the O2 positive electrode material within the test voltage range of 1.5 to 4.5 V (vs. Na+ / Na) are as high as 166 and 211 mAh / g, respectively. Figure 4 The first 50 cycles of the sodium ion battery assembled with the positive electrode material prepared in Example 1 at a current density of 0.1C are shown in FIG. Figure 4 It can be seen that the reversible capacity retention rate of the material after 50 cycles is as high as 97.5%, indicating that it has excellent electrochemical reversibility.
[0079] Example 2
[0080] According to the element molar ratio of 0.66:0.18:0.57:0.05:0.05:0.05:0.05:0.05, sodium acetate, nickel acetate, manganese acetate, zinc acetate, copper acetate, magnesium acetate, aluminum nitrate and niobium oxalate are accurately weighed respectively (wherein the amount of sodium acetate is 5% excess on the basis of the theoretical molar amount); citric acid is dissolved in 30 mL of deionized water, and the molar amount of citric acid is 1.5 times the molar amount of metal ions; the above metal salts are added to the citric acid solution and stirred at room temperature for 30 minutes; 25-28% mass fraction of ammonia water is added dropwise until the pH value of the mixed solution is adjusted to 7; the mixed solution is placed in a water bath at 80°C and heated and stirred to obtain a wet gel; the obtained wet gel is transferred to a 120°C blast oven and dried for 10 hours; and a gel precursor is obtained after uniform grinding. The gel precursor was pressed into a sheet and placed in a tube furnace for pre-calcination at a rate of 5°C / min to 450°C for 6 hours, cooled naturally to room temperature, ground and pressed into a sheet, and then heated to 900°C for 12 hours at a rate of 5°C / min, cooled naturally to room temperature, and the cooled product was ground to obtain a layered high entropy oxide positive electrode material for sodium ion batteries, whose chemical formula is Na 0.66 Ni 0.18 Mn 0.57 Zn 0.0 5Cu 0.05 Mg 0.05 Al 0.05 Nb 0.05 O2.
[0081] Figure 5 This is the XRD pattern of the obtained layered high entropy oxide positive electrode material for sodium ion batteries. Figure 5 The results in show that the cathode material is P2 pure phase.
[0082] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Figure 6 The first five cycles of charge and discharge curves of the obtained button battery at a current density of 0.1C are shown in the attached figure. Figure 6 As shown, Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Al 0.05 Nb 0.05 O2 cathode material is 1.5~4.5V(vs.Na + / Na) within the test voltage range, the first charge and discharge capacities are as high as 137 and 176 mAh / g, respectively.
[0083] Figure 7The cycle performance diagram of the sodium ion battery assembled with the positive electrode material prepared in Example 2 at a current density of 0.1C for the first 50 cycles is shown in FIG. Figure 7 It can be seen that the reversible capacity of the material after 5 cycles is 168 mAh / g, and the capacity retention rate is 95%. The reversible capacity retention rate of the material after 50 cycles is still as high as 90.6%, indicating that its electrochemical reversibility is high.
[0084] Comparative Example 1
[0085] According to the element molar ratio of 1:0.2:0.2:0.2:0.2:0.1:0.1, sodium acetate, ferric acetate, manganese acetate, nickel acetate, tetrabutyl titanate, zirconium isopropoxide and lithium acetate are accurately weighed respectively (wherein, the amount of sodium acetate is 5% excess on the basis of the theoretical molar amount); citric acid is dissolved in 30 mL of deionized water, and the molar amount of citric acid is 1.5 times the molar amount of metal ions; the above metal salts are added to the citric acid solution and stirred at room temperature for 30 minutes; 25-28% mass fraction of ammonia water is added dropwise until the pH value of the mixed solution is adjusted to 7; the mixed solution is placed in a water bath at 80°C and heated and stirred to obtain a wet gel; the obtained wet gel is transferred to a 120°C forced air oven and dried for 10 hours; and a gel precursor is obtained after uniform grinding. The gel precursor was pressed into a sheet and placed in a tube furnace for pre-calcination at a rate of 5°C / min to 450°C for 6 hours, cooled naturally to room temperature, ground and pressed into a sheet, and then heated to 900°C for 12 hours at a rate of 5°C / min, cooled naturally to room temperature, and the cooled product was ground to obtain a layered high entropy oxide positive electrode material for sodium ion batteries. The chemical formula of the positive electrode material O3-NaFe 0.2 Mn 0.2 Ni 0.2 Ti 0.2 Zr 0.1 Li 0.1 O2.
[0086] Figure 8 The XRD pattern of the obtained layered high entropy oxide cathode material for sodium ion batteries is shown in Figure 1. Each characteristic diffraction peak is clearly visible, and all conform to the space group R-3m, indicating that the cathode material is an O3 phase.
[0087] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Fig. 9 The first five cycles of charge and discharge curves of the obtained button battery at a current density of 0.1C are shown in the attached figure. Fig. 9 As shown, O3-NaFe 0.2 Mn 0.2 Ni 0.2 Ti 0.2 Zr 0.1 Li 0.1O2 cathode material is 1.5~4.5V(vs.Na + / Na), the first reversible discharge capacity was only 100 mAh / g, and the reversible capacity decayed to ~75 mAh / g after 5 cycles, indicating poor cycle stability.
[0088] Comparative Example 2
[0089] According to the element molar ratio of 0.66:0.3:0.3:0.1:0.1:0.1:0.1, sodium acetate, ferrous acetate, manganese acetate, nickel acetate, magnesium acetate, zinc acetate and copper acetate are accurately weighed respectively (wherein, the amount of sodium acetate is 5% excess on the basis of the theoretical molar amount); citric acid is dissolved in 30 mL of deionized water, and the molar amount of citric acid is 1.5 times the molar amount of metal ions; the above metal salts are added to the citric acid solution and stirred at room temperature for 30 minutes; 25-28% mass fraction of ammonia water is added dropwise until the pH value of the mixed solution is adjusted to 7; the mixed solution is placed in a water bath at 80°C and heated and stirred to obtain a wet gel; the obtained wet gel is transferred to a 120°C forced air oven and dried for 10 hours; and a gel precursor is obtained after uniform grinding. The gel precursor was pressed into a sheet and placed in a tube furnace at a rate of 5°C / min to 300°C for pre-calcination for 12 hours, cooled naturally to room temperature, ground and pressed into a sheet, and then heated to 625°C at a rate of 5°C / min for calcination for 12 hours, cooled naturally to room temperature, and the cooled product was ground to obtain a layered high entropy oxide positive electrode material for sodium ion batteries. The chemical formula of the positive electrode material P3-Na 0.66 Fe 0.3 Mn 0.3 Ni 0.1 Mg 0.1 Zn 0.1 Cu 0.1 O2.
[0090] Fig.10 The XRD pattern of the obtained layered high entropy oxide cathode material for sodium ion batteries is shown in Figure 1. Each characteristic diffraction peak is clearly visible, and all conform to the space group Cm, indicating that the cathode material is a P3 phase.
[0091] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Fig.11 The first five cycles of charge and discharge curves of the obtained button battery at a current density of 0.1C are shown in the attached figure. Fig.11 As shown, P3-Na 0.66 Fe 0.3 Mn 0.3 Ni 0.1 Mg 0.1 Zn 0.1 Cu 0.1 O2 cathode material is 1.5~4.5V(vs.Na+ / Na) within the test voltage range, the first charge and discharge capacity is only 166mAh / g and 205mAh / g. Fig.12 This is a cycle performance diagram of the first 50 cycles of a sodium ion battery assembled with the positive electrode material prepared in Comparative Example 2 at a current density of 0.1C. The results show that the reversible capacity retention rate of the material after 50 cycles is 74.6%, which is poorer than the cycle stability of Examples 1 and 2.
[0092] Comparative Example 3
[0093] According to the element molar ratio of 0.66:0.6:0.1:0.3, sodium acetate, manganese acetate, nickel acetate and magnesium acetate are accurately weighed respectively (wherein, the amount of sodium acetate is 5% excess on the basis of the theoretical molar amount); citric acid is dissolved in 30 mL of deionized water, and the molar amount of citric acid is 1.5 times the molar amount of metal ions; the above metal salts are added to the citric acid solution and stirred at room temperature for 30 minutes; 25-28% mass fraction of ammonia water is added dropwise until the pH value of the mixed solution is adjusted to 7; the mixed solution is placed in a water bath at 80°C and heated and stirred to obtain a wet gel; the obtained wet gel is transferred to a 120°C blast oven and dried for 10 hours; and a gel precursor is obtained after uniform grinding. The gel precursor was pressed into a sheet and placed in a tube furnace for pre-calcination at a rate of 5°C / min to 450°C for 6 hours, cooled naturally to room temperature, ground and pressed into a sheet, and then heated to 900°C for 12 hours at a rate of 5°C / min, cooled naturally to room temperature, and the cooled product was ground to obtain a layered high entropy oxide positive electrode material for sodium ion batteries. The chemical formula of the positive electrode material P2-Na 0.66 Mn 0.6 Ni 0.1 Mg 0.3 O2.
[0094] Fig.13 The XRD pattern of the obtained sodium ion battery layered high entropy oxide cathode material is shown in Figure 1. Each characteristic diffraction peak is clearly visible, all of which conform to the space group P63 / mmc, and there are no extra diffraction peaks in the XRD spectrum, indicating that the cathode material is a pure P2 phase.
[0095] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Fig.14 The first five cycles of charge and discharge curves of the obtained button battery at a current density of 0.1C are shown in FIG. Fig.14 As shown, P2-Na 0.66 Mn 0.6 Ni 0.1 Mg 0.3 O2 cathode material is 1.5~4.5V(vs.Na + / Na), the first reversible charge and discharge capacities were only 131 mAh / g and 142 mAh / g, which were significantly lower than the corresponding values in Examples 1 and 2.
[0096] Comparative Example 4
[0097] The synthesis method used in Comparative Example 1 is a high temperature solid phase synthesis method, which is as follows:
[0098] According to the element molar ratio of 2:1:2, the corresponding mass of sodium carbonate, nickel dioxide and manganese dioxide are accurately weighed as precursors (wherein the amount of sodium carbonate is 5% excess on the basis of the theoretical molar amount), the raw materials are added to an agate ball mill, and then grinding balls with a total mass of 12 times the total mass of the mixed materials are added thereto, and the precursor materials are mixed evenly at a speed of 600rpm for 15h; the ball-milled mixed materials are pressed into a disc with a diameter of 14mm under a pressure of 15MPa; the obtained sheet sample is placed in a tubular furnace, heated to 900℃ at a rate of 5℃ / min in an oxygen atmosphere, and calcined for 12h; cooled to room temperature with the furnace, and the positive electrode material Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2.
[0099] The obtained positive electrode material was subjected to XRD test to determine the phase. The test results are as follows: Fig.15 As shown, Fig.15 The results show that the Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 is pure P2 phase.
[0100] Fig.16 This is the SEM image of the positive electrode material obtained in Comparative Example 4. Fig.16 It can be seen that the obtained material has agglomerated.
[0101] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Fig.17 The first five charge and discharge curves of the button battery obtained in Comparative Example 4 at a current density of 0.1C are shown in the attached figure. Fig.17 As shown, there are multiple voltage steps in the first five cycles of the electrochemical curves, which indicates that there are complex phase changes during the charge and discharge process, indicating that the structural stability of the material is poor, resulting in serious capacity loss.
[0102] Comparative Example 5
[0103] The synthesis method used in Comparative Example 5 is a high temperature solid phase synthesis method, which is as follows:
[0104] According to the molar ratio of elements of 1:0.5:0.4:0.1, the corresponding masses of sodium carbonate, manganese dioxide, nickel oxide and zinc acetate were accurately weighed as precursors (wherein the amount of sodium carbonate was 5% in excess of the theoretical molar amount), added to an agate ball mill, and then added grinding balls with a total mass of 12 times the total mass of the mixed materials, and ball milled at a speed of 600rpm for 15h to mix the above precursor materials evenly; the ball-milled mixed materials were pressed into a disc with a diameter of 14mm under a pressure of 15MPa; the obtained sheet sample was placed in a tubular furnace, heated to 900℃ at a rate of 5℃ / min in an oxygen atmosphere, and calcined for 12h; cooled to room temperature with the furnace, and the positive electrode material NaMn 0.5 Ni 0.4 Zn 0.1 O2.
[0105] The obtained positive electrode material was subjected to XRD test to determine the phase. The test results are as follows: Fig.18 As shown, Fig.18 The results show that the NaMn 0.5 Ni 0.4 Zn 0.1 O2 is pure O3 phase.
[0106] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Fig.19 The first five charge and discharge curves of the button battery obtained in Comparative Example 5 at a current density of 0.1C are shown in the attached figure. Fig.19 It is shown that there are multiple voltage steps in the electrochemical curves of the first five cycles. The first reversible discharge capacity is only 171 mAh / g, and the reversible capacity decays to 151 mAh / g after 5 cycles. This indicates that there is a complex phase change in the charge and discharge process, which makes the structural stability of the material poor, resulting in serious capacity loss.
[0107] Comparative Example 6
[0108] The synthesis method used in Comparative Example 6 is a high-temperature solid phase synthesis method, which is as follows:
[0109] According to the element molar ratio of 0.67:0.21:0.12:0.67, the corresponding mass of sodium carbonate, nickel oxide, zinc acetate and manganese dioxide were accurately weighed as precursors (wherein the amount of sodium carbonate was 5% excess on the basis of the theoretical molar amount), added to an agate ball mill, and then added grinding balls with a total mass of 12 times the total mass of the mixed material, and ball milled at a speed of 600rpm for 15h to mix the above precursor materials evenly; the ball-milled mixed material was pressed into a disc with a diameter of 14mm under a pressure of 15MPa; the obtained sheet sample was placed in a tubular furnace, heated to 650℃ at a rate of 5℃ / min in an oxygen atmosphere, and calcined for 15h; cooled to room temperature with the furnace to obtain the positive electrode material P3-Na 0.67 Ni 0.21 Zn 0.12 Mn 0.67 O2.
[0110] The obtained positive electrode material was subjected to XRD test to determine the phase. The test results are as follows: Fig. 20 As shown, Fig. 20 The results show that the NaMn 0.5 Ni 0.4 Zn 0.1 O2 is a P3 phase, but the crystallinity is not high and there are impurity peaks.
[0111] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Fig.21 The first five charge and discharge curves of the button battery obtained in Comparative Example 6 at a current density of 0.1C are shown in the attached figure. Fig.21 As shown, there are multiple voltage steps in the first five cycles of the electrochemical curve. The first reversible discharge capacity is only 119 mAh / g. The reversible capacity decays to 105 mAh / g after 5 cycles, indicating that the material has poor cycle stability.
[0112] Comparative Example 7
[0113] The molecular formula of the positive electrode material prepared in Comparative Example 7 is the same as that in Example 1, except that the synthesis method adopted in Comparative Example 7 is a high-temperature solid-phase synthesis method, which is as follows:
[0114] According to the molar ratio of elements of 0.66: 0.18: 0.57: 0.05: 0.05: 0.05: 0.05: 0.05, accurately weigh the corresponding mass of sodium carbonate, nickel dioxide, manganese dioxide, zinc acetate, copper oxide, magnesium oxide and titanium dioxide as precursors (wherein the amount of sodium carbonate is 5% excess on the basis of the theoretical molar amount), add them into an agate ball mill, then add grinding balls with a total mass 12 times the total mass of the mixed materials, ball mill at a speed of 600rpm for 15h to mix the above precursor materials evenly; the ball-milled mixed materials are pressed into a disc with a diameter of 14mm under a pressure of 15MPa; the obtained sheet sample is placed in a tubular furnace, heated to 900℃ at a rate of 5℃ / min in an oxygen atmosphere, and roasted for 12h; cooled to room temperature with the furnace to obtain a sodium ion battery layered high entropy oxide positive electrode material, whose chemical formula is Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Ti 0.1 O2.
[0115] The obtained positive electrode material was subjected to XRD test to determine the phase. The test results are as follows: Fig. 22 As shown, Fig. 22 The results show that the Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Ti 0.1 O2 is P2 phase.
[0116] Fig.23 This is the SEM image of the positive electrode material obtained in Comparative Example 2. Fig.23 It can be seen that the obtained material has agglomerated.
[0117] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Fig.24 The first five charge and discharge curves of the button battery obtained in Comparative Example 7 at a current density of 0.1C; Fig.24 As shown, Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Ti 0.1 O2 cathode material is 1.5~4.5V(vs.Na + / Na), the initial charge and discharge capacities were 124 and 175 mAh / g, and the reversible capacity after 5 cycles was 155 mAh / g.
[0118] Comparative Example 8
[0119] The molecular formula of the positive electrode material prepared in Comparative Example 8 is the same as that in Example 2, except that the synthesis method adopted in Comparative Example 8 is a high-temperature solid-phase synthesis method, which is as follows:
[0120] According to the molar ratio of elements of 0.66:0.18:0.57:0.05:0.05:0.05:0.1, the corresponding masses of sodium carbonate, nickel dioxide, manganese dioxide, zinc acetate, copper oxide, magnesium oxide, aluminum oxide and niobium oxalate were accurately weighed as precursors (wherein the amount of sodium carbonate was 5% excess on the basis of the theoretical molar amount), added to an agate ball mill, and then added grinding balls with a total mass of 12 times the total mass of the mixed materials, and ball milled at a speed of 600rpm for 15h to mix the above precursor materials uniformly; the ball-milled mixed materials were pressed into a disc with a diameter of 14mm under a pressure of 15MPa; the obtained sheet sample was placed in a tubular furnace, heated to 900℃ at a rate of 5℃ / min in an oxygen atmosphere, and calcined for 12h; cooled to room temperature with the furnace to obtain a sodium ion battery layered high entropy oxide positive electrode material, whose chemical formula is Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Al 0.05 Nb 0.05 O2.
[0121] The obtained positive electrode material was subjected to XRD test to determine the phase. The test results are as follows: Fig.25 As shown, Fig.25 The results show that the Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Al 0.05 Nb 0.05 O2 is P2 phase.
[0122] Fig.26 This is the SEM image of the positive electrode material obtained in Comparative Example 8. Fig.26 It can be seen that the obtained material has agglomerated.
[0123] According to the method in Example 1, the obtained positive electrode material was prepared into a button-type battery, and a charge and discharge test was performed at room temperature. Fig. 27The first five charge and discharge curves of the button battery obtained in Comparative Example 8 at a current density of 0.1C are shown in FIG. Fig. 27 As shown, Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Al 0.05 Nb 0.05 O2 cathode material is 1.5~4.5V(vs.Na + / Na), the initial charge and discharge capacities were 132 and 162 mAh / g respectively, the reversible capacity after 5 cycles was 153 mAh / g, and the capacity retention rate was 94%.
[0124] By comparing Examples 1 to 2 and Comparative Examples 1 to 2, it can be seen that the sodium ion battery layered high entropy oxide positive electrode material with P2 phase has a high reversible capacity and good structural stability. By comparing Examples 1 to 2 and Comparative Example 3, it can be seen that when the M element is four or more, the obtained sodium ion battery layered high entropy oxide positive electrode material has better electrochemical performance. By comparing Examples 1 to 2 and Comparative Examples 4 to 8, it can be seen that the present invention adopts a sol-gel method to prepare the positive electrode material, the preparation method is simple, and it is easy to realize large-scale production, and the obtained positive electrode material is significantly superior to the material prepared by the ordinary high-temperature solid phase method in terms of reversible capacity and electrochemical reversibility.
[0125] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A layered high entropy oxide cathode material for sodium ion batteries, It is characterized in that The general chemical formula is shown in Formula I: Na x Ni a Mn b M c O 2 Formula I; In formula I: 0.6≤x≤0.7, 0.15≤a<0.33, 0.5≤b<0.67, 0<c≤0.35, a+b+c=1, M is at least four of Li, Zn, Cu, Mg, Ca, Fe, Al, Co, Y, Ru, Ti, Ir, Sb, Te, Sn, and Nb; The layered high entropy oxide positive electrode material is a P2 phase.
2. The layered high entropy oxide positive electrode material for sodium ion batteries according to claim 1, It is characterized in that M is at least four of Zn, Cu, Mg, Al, Ti, Sn and Nb.
3. The layered high entropy oxide positive electrode material for sodium ion batteries according to claim 1, It is characterized in that The sodium ion battery layered high entropy oxide positive electrode material is Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Ti 0.1 O 2 and Na 0.66 Ni 0.18 Mn 0.57 Zn 0.05 Cu 0.05 Mg 0.05 Al 0.05 Nb 0.05 O 2 At least one of .
4. The method for preparing the layered high entropy oxide positive electrode material for sodium ion batteries according to any one of claims 1 to 3, It is characterized in that The following steps are involved: Mixing a sodium source, a nickel source, a manganese source, a soluble compound corresponding to the M element and a citric acid solution, adjusting the pH value of the resulting mixed solution to 7 to 8, and then heating and stirring to obtain a gel precursor; The gel precursor is pre-calcined and calcined in sequence to obtain the sodium ion battery layered high entropy oxide positive electrode material.
5. The preparation method according to claim 4, It is characterized in that The molar ratio of citric acid to metal ions in the mixed solution is (1.2-1.5):1, and the molar amount of the metal ions is calculated based on the total molar amount of sodium ions, nickel ions, manganese ions and M ions.
6. The preparation method according to claim 4, It is characterized in that The heating and stirring temperature is 60-80° C., the stirring speed is 400-800 rpm, and the time is 2-6 hours.
7. The preparation method according to claim 4, It is characterized in that The method further comprises obtaining a wet gel after heating and stirring, and drying the wet gel and then grinding it to obtain a gel precursor.
8. The preparation method according to claim 4, It is characterized in that The pre-calcination temperature is 350-500°C and the time is 5-12h; The calcination temperature is 800-900° C. and the calcination time is 10-16 hours.
9. A positive electrode sheet, It is characterized in that It comprises the sodium ion battery layered high entropy oxide positive electrode material as described in any one of claims 1 to 3 or the sodium ion battery layered high entropy oxide positive electrode material prepared by the preparation method as described in any one of claims 4 to 8.
10. A sodium ion battery, It is characterized in that Including the positive electrode sheet as described in claim 9.
Citation Information
Cited By
P2-type medium-entropy layered oxide positive electrode material and preparation method and application thereof
CN119890294A
Manganese-based layered oxide positive electrode material and preparation method and application thereof
CN120191967A
Sodium ion layered oxide positive electrode material and preparation method thereof
CN120784355A
High-entropy doped P2 type layered oxide positive electrode material, preparation method thereof and battery positive electrode
CN121617955A
A high-entropy doped p2-type layered oxide positive electrode material, a preparation method thereof and a battery positive electrode
CN121617955B
